Integrated structural health monitoring of highway bridges in Singapore - Tjin, Swee Chuan (2008)
The main objective of this project is to carry out the research and development of fibre Bragg grating (FBG) strain sensors and the testing of the FBG strain sensors in civil engineering structures. The FBG strain sensors were embedded using reinforced carbon-fibre composite laminates to increase their robustness as well as their performance advantages over the bare FBG strain sensors which include better linearity, higher accuracy, wider sensing range, lower thermal conductivity and expansion coefficient. A full-scale column specimen (or a civil-engineering structure) was designed, fabricated and tested for its suitable use in the testing of the embedded FBG strain sensors. The FBG strain sensors were calibrated by mounting them onto the surface of a reinforcement rebar alongside the electrical strain gauges, and excellent linearity (which is an important desirable feature) of the output response of the FBG strain sensor against the input applied load was observed. Quasi-static load test and dynamic impulse load test were carried out on the FBG strain sensors. It was found that the performances of the FBG strain sensors are comparable with those of the electrical strain gauges, demonstrating the very good performances of the FBG strain sensors. Note that the FBG strain sensors have several unique advantages over the electrical strain gauges which include electrical isolation to prevent electrical shock, elimination of conductive paths in high voltage environments, immunity to electromagnetic interference (EMI), and the ability to withstand extreme vibration and even shock.